Pengaruh Work Life Balance dan Stres Kerja terhadap Kinerja Karyawan Generasi Z: (Studi pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Bhayangkara Jakarta Raya Angkatan 2020) - Shinta Ramadhani Berliana Nasution; Agus Dharmanto; Nita Komala Dewi (International Forum of Researchers and Lecturers, 2024)
The purpose of this study is to determine the Influence of Work-Life Balance and Work Stress on the Performance of Generation Z Employees (Study of students from the Faculty of Economics and Business Bhayangkara Jakarta Raya University Class of 2020). The method used in this study is a quantitative method with a type of survey method. The number of samples used in this study uses the calculation of the slovin formula as many as 100 respondents. The data processing tool used in this study is using SPSS software version 27. The results in this study show that the work-life balance variable partially has a significant effect on employee performance, the work stress variable partially has a significant effect on employee performance. The results in this study show that the variables of work life balance and work stress simultaneously have a significant effect on employee performance.